Modern Contraceptive Use in District : Crossectional Study - Yanna Wari Harahap; Arinil Hidayah; Febrina Angraini Simamora (Journal of Public Health and Pharmacy, 2021)
Trend contraceptive use in Indonesia is higher from 49,7% in 1997 and 61,9% in 2012, but it becomes 61,1% in 2015. But Modern contraceptive use is high in short-term contraception and skewed method mix in one method. The skewed method is influenced by the quality of the program. The aim of the study describe modern contraceptive use and quality of service family planning in the district. A cross-sectional study using PMA2020 survey data conducted from May to October 2015 in Indonesia. The sample was woman sexual active respondents and health care has chosen using two stages stratified random sampling. The result of the study showed percentage of modern contraceptive use was the skewed method (93%). The skewed method was in injection contraceptive (62,4%). Service environment index in district is 75% inadequate. Service environment index family planning in district showed inadequate (75%), availability contraceptive methods in district is less than 5 methods (69%). The result described inadequate service environment index showed skewed contraceptive used (94,7%). District that has not adequate service environment is higher skewed method than adequate service environment. Improve service environment quality family can help women to choose suitable contraceptive.